ANTI-ASTHMA ACTIVITY OF TAMARIND PULP EXTRACT (TAMARINDUS INDICA L.) - MAHMUDAH, RIFA’ATUL; ADNYANA, I KETUT; KURNIA, NENGFISHERI (International Journal of Current Pharmaceutical Research, 2017)
Objective: Tamarind (Tamarindusindica L.) is one of the plants, which most of its parts are not only rich in nutrients, but also has been used widely in the community as a medicine, and one of them is believed to have effectiveness as anti-asthma. Methods: The study of that anti-asthma activity was conducted by using the test method of improvement breathing patterns in the male guinea pig and using anti-inflammatory testing in male Wistar rats. Results: The results of breathing patterns improvement test shows that there is no significant difference of breath intensity between observation groups (extract in doses of 25 mg/kg bw guinea pig, 75 mg/kg bw guinea pig, and 225 mg/kg bw guinea pig) and the control group. However, it has significant differences (p<0.05) in the decline of breath frequency, in line with the effect that given by methylprednisolone 4.5 mg/kg bw guinea pig and salbutamol 4 mg/kg bw guinea pig. While the result of anti-inflammatory test shows the significant decrease in inflammation percentage in each of observation group (extract in doses of 25 mg/kg bw rat, 75 mg/kg bw rat, and 225 mg/kg bw rat) than the control group at minute 30 up to 360, it is in line with the reduction effect given by methylprednisolone 4.5 mg/kg bw rat. Conclusion: The best effect in breathing patterns improvements and anti-inflammatory are demonstrated by extract in a dose of 75 mg/kg bw. One of the anti-asthma mechanisms is an anti-inflammatory effect.